Pemutusan Hubungan Kerja oleh Pihak Perusahaan dalam Pandangan Majelis Ulama Indonesia (Studi Analisis Fatwa MUI No. 149/DSN/VI/2022) - Lisa Dwina Fitri; Fauziah Ramdani; Sa’adal Jannah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to find out the considerations and decisions of the Indonesian Ulema Council (MUI) in legal matters regarding the provision of insurance to employees who have been laid off due to a bankrupt company. This research uses descriptive-qualitative research that focuses on manuscript and text studies. The results of the research found are as follows: first, the law of layoff insurance products due to bankruptcy companies is permissible as long as the insurance provided follows the provisions set by the MUI and does not violate the principles of sharia insurance. Second, the Indonesian Ulema Council (MUI) in compiling and establishing fatwa number 149 of 2022 uses the istiṣlāh or maslahah al-mursalah method. This determination is in accordance with the objectives of maqāṣid al-syarῑ'ah. In insurance, the maqāṣid al-syarῑ'ah of the permissibility of an insurance contract include maintaining religion where the implementation of sharia insurance must be in accordance with sharia principles, protecting the life of the insurance participant taking care of himself and his family if one day he is laid off and unable to meet his needs, insurance the sharia that he does is part of guarding the soul, guarding the mind, which can be seen from sharia insurance helping insurance participants in controlling their desires from carrying out insurance contracts that are not in accordance with Islamic law, protecting assets, namely by the existence of the principle of sharia insurance by prohibiting usury in This insurance is part of protecting assets, protecting offspring, namely by maintaining religion, soul, mind, and assets, the insurance that applies can be ensured that it is halal for him to give to his family.